2011
DOI: 10.1177/1087724x11419306
|View full text |Cite
|
Sign up to set email alerts
|

Defining Complex Project Management of Large U.S. Transportation Projects

Abstract: The management of complex transportation projects requires a fundamental change in how they are approached. The traditional methodology for managing cost, schedule, and design, on transportation projects is not adequate for complex projects. A five-dimensional model has been developed adding context and finance, which have previously been regarded merely as external risks. The five-dimensional model has been developed from an extensive literature search pertaining to the management of complex transportation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Many researchers have described complexity as a critical topic in the area of project management research (Gidado, 1996;Hass, 2008;Owens, Ahn, Shane, Strong, & Gransburg, 2011;Bosch-Rekveldt, 2011;Lehtiranta, 2011;Puddicombe, 2012;Ahern, Leavy, & Byrne, 2013;Lu et al, 2015;Abdou et al, 2016;Kiridena & Sense, 2016;Ji, AbouRizk, Zaiane, & Li, 2018). The meaning of the word "complexity" was ambiguous and lacked a standard definition for many years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many researchers have described complexity as a critical topic in the area of project management research (Gidado, 1996;Hass, 2008;Owens, Ahn, Shane, Strong, & Gransburg, 2011;Bosch-Rekveldt, 2011;Lehtiranta, 2011;Puddicombe, 2012;Ahern, Leavy, & Byrne, 2013;Lu et al, 2015;Abdou et al, 2016;Kiridena & Sense, 2016;Ji, AbouRizk, Zaiane, & Li, 2018). The meaning of the word "complexity" was ambiguous and lacked a standard definition for many years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the project complexity is difficult to be quantified precisely, many researchers identified complexity factors to build a framework describing the project complexity qualitatively. For instance, Sinha et al (2006, Xia and Chan (2012), Lessard et al (2014), Maylor et al (2008), Gransberg et al (2012), Vidal and Marle (2008), Owens et al (2012), Jarkas (2017), and Luo et al (2016) mainly focus on the framework of project complexity from different views. In addition, several attempts have been made to propose methods to measure the project complexity quantitatively such as Vidal et al (2011b), Nguyen et al (2015), He et al (2015), Shafiei-Monfared and Jenab (2012), Lu et al (2015), Qureshi and Kang (2015), and Ellinas et al (2018).…”
Section: Literature Review On Project Complexity Measurementmentioning
confidence: 99%
“…The time pressure explanation can also be found in the literature. Owens, Ahn, Shane, Strong, and Gransberg (2012) found that tight timelines for project delivery add to the complexity of the project. When managers experience time pressure, they draw boundaries in attempts to reduce the complexity of implementation.…”
Section: Internally-and Externally Oriented Management In Responding mentioning
confidence: 99%